Peran NGO sebagai Kelompok Penekan di Pemerintahan Domestik EU dalam Kebijakan FLEGT-VPA EU - , GEMILANG HAIFA KHAIRINISSA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research analyze the role of NGO as pressure group in European Union (EU) governance in the EUâs policy making process of Forest Law Enforcement, Governance and Trade - Voluntary Partnership Agreements (FLEGT-VPA). FLEGT-VPA is one of solution that agreed by international society in Bali Declaration 2001 to combat illegal logging issues that increased in developing country that produced timber to fulfill the demand of international timber trade. EU as one of active players, especially as an importer, in international timber trade then certainly has international societyâs eyes on them. With his big number of international timber tradeâs graph, EU then officially made an action plan of FLEGT in 2003. As a pressure group, even in EUâs governance that already has a legal policy to increase the role of NGOs, NGOs still has a limitation function and power in order to penetrate EUâs policy making process. Moreover, EU has many state members that have a heterogeneous style of governance that make it harder for NGOs to penetrate. This situation then make some of NGOs like Greenpeace, FoE, Fern, and WWF, try to do a way around by influence international society first, then try to penetrate EU with a global collective action by international society. Using their transnational network around the world, they try to make a global collective action by advocating international society.